A Magnetometer Based on a Spin Wave Interferometer - Balynsky, M. (Sci Rep, 2017)
We describe a magnetic field sensor based on a spin wave interferometer. Its sensing element consists of a magnetic cross junction with four micro-antennas fabricated at the edges. Two of these antennas are used for spin wave excitation while two other antennas are used for detection of the inductive voltage produced by the interfering spin waves. Two waves propagating in the orthogonal arms of the cross may accumulate significantly different phase shifts depending on the magnitude and direction of the external magnetic field. This phenomenon is utilized for magnetic field sensing. The sensitivity attains its maximum under the destructive interference condition, where a small change in the external magnetic field results in a drastic increase of the inductive voltage, as well as in the change of the output phase. We report experimental data obtained for a micrometer scale Y(3)Fe(2)(FeO(4))(3) cross structure. The change of the inductive voltage near the destructive interference point exceeds 40 dB per 1 Oe. The phase of the output signal exhibits a π-phase shift within 1 Oe. The data are collected at room temperature. Taking into account the low thermal noise in ferrite structures, we estimate that the maximum sensitivity of the spin wave magnetometer may exceed attotesla.